2017
DOI: 10.3329/bjz.v44i2.32760
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density on growth of zebrafish (Danio rerio, Hamilton, 1822)

Abstract: Abstract:The effect of stocking density on growth of zebra fish was examined.Total five different stocking densities (5, 15, 25, 35 and 45 individuals per 2 liters of water) were maintained in triplicate for a period of 60 days. One month old zebrafish were randomly stocked into 15 tanks and fish were fed with commercial diet. The mean weight gain, specific growth rate and length gain for treatment 1 (5 fish/2liter) and treatment 2 (15 fish/2 liter) were significantly (p < 0.05) higher than treatment 3 (25 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
5
1
Order By: Relevance
“…That fish from enriched and bare tanks were of similar length at 30 dpf was contrary to expectations. However, this may be explained by the fact that fewer larvae survived in bare tanks than in enriched and as an equal overall tank food ration was provided, more resources would have been available per fish for the fish in the bare tanks and stocking density is known to affect growth rate (including length gain) in D. rerio (Rabbane et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…That fish from enriched and bare tanks were of similar length at 30 dpf was contrary to expectations. However, this may be explained by the fact that fewer larvae survived in bare tanks than in enriched and as an equal overall tank food ration was provided, more resources would have been available per fish for the fish in the bare tanks and stocking density is known to affect growth rate (including length gain) in D. rerio (Rabbane et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Zebrafish behavior was observed at days 14 ± 1 (novel tank, mirror biting, predator avoidance, social interaction, and shoaling tests), 17 (color preference test), 19 (circadian locomotor activity test), and 21 (biochemical assay). All of the zebrafish in each group in every experiment were kept in a 4 L tank as, based on prior studies, this stocking density of zebrafish for the long-term helps to maintain low stress levels, with the assumption that all of the fish received equal amounts of the carrier [25][26][27][28]. Incubation water was changed every day and the donepezil concentration was maintained during incubation in all of the experiments.…”
Section: Preparation and Exposure To Donepezil Hclmentioning
confidence: 99%
“…The optimal holding density for growth in that study was therefore concluded to 4.2 fish/L. On the contrary, when Rabbane et al 20 investigated growth in relation to density, they received a different result. They found the growth rate and length gain to not be significantly different between 2.5 and 7.5 fish/L, while both variations generated significantly higher results than holding densities of 12.5, 17.5, and 22.5 fish/L.…”
Section: Growthmentioning
confidence: 80%